In Search of Red Noctiluca scintillans Blooms in the East China Sea. Issue 11 (12th June 2019) - Qi, Lin; Tsai, Sheng‐Fang; Chen, Yanlong; Le, Chengfeng; Hu, Chuanmin
Abstract: Red Noctiluca scintillans ( RNS ) is one of the major species causing red tides and bioluminescence, yet extremely difficult to track due to its ephemeral nature. Here, we show that RNS can be fingerprinted from satellite data due to its unique absorption and scattering properties. Retrospective analysis of Moderate Resolution Imaging Spectroradiometer data of 2000–2017 over the East China Sea reveals seasonal patterns and interannual changes as well as an increasing RNS bloom trend, all driven by hydrographical and biological factors and possibly by the construction of the Three Gorges Dam. Unlike earlier reports from field measurements, RNS blooms are found in both coastal and offshore waters of the ECS, to at least 126°E (> 330 km from the Yangtze River mouth). RNS blooms are also found in August and September where water temperature of 28–30 °C is well beyond the earlier reported range of 10–25 °C. Key Points: Red Noctiluca scintillans ( RNS ), which feeds on other algae, can be fingerprinted from satellite imagery The technique can be applied to nearly all existing sensors, regardless of number of bands or spatial resolution Long‐term distributions of RNS blooms in the ECS provide unprecedented knowledge on their locations and environments